2009
DOI: 10.1152/japplphysiol.91062.2008
|View full text |Cite
|
Sign up to set email alerts
|

Responses of LDL and HDL particle size and distribution to omega-3 fatty acid supplementation and aerobic exercise

Abstract: The purpose of this investigation was to determine the independent and combined effects of aerobic exercise and omega-3 fatty acid (n-3fa) supplementation on lipid and lipoproteins. Sedentary, normoglycemic, nonsmoking men (n = 11) were assigned to perform rest and exercise before and during n-3fa supplementation. Exercise consisted of 3 consecutive days of treadmill walking at 65% maximum O(2) consumption for 60 min. Supplementation consisted of 42 days of 4.55 g/day of n-3fa. A two-way factorial ANOVA with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
4
16
0
1
Order By: Relevance
“…In turn, the accelerated catabolism increases the availability of triglycerides for exchange with the HDL compartment; this mechanism might explain our observed increasing large and decreasing small and medium HDL concentrations and higher particle size with higher intakes of n23 fatty acids. This finding is also consistent with previous studies of n23 fatty acid supplementation showing that the cholesterol content shifts from HDL3 particles to the larger HDL2 particles (27). In the presence of enhanced catabolism of large VLDLs, reduced cholesteryl ester transfer protein activity (28) would be expected to reduce the triglyceride and cholesterol ester exchange with HDL.…”
Section: Discussionsupporting
confidence: 92%
“…In turn, the accelerated catabolism increases the availability of triglycerides for exchange with the HDL compartment; this mechanism might explain our observed increasing large and decreasing small and medium HDL concentrations and higher particle size with higher intakes of n23 fatty acids. This finding is also consistent with previous studies of n23 fatty acid supplementation showing that the cholesterol content shifts from HDL3 particles to the larger HDL2 particles (27). In the presence of enhanced catabolism of large VLDLs, reduced cholesteryl ester transfer protein activity (28) would be expected to reduce the triglyceride and cholesterol ester exchange with HDL.…”
Section: Discussionsupporting
confidence: 92%
“…[127][128][129] These lifestyle change interventions have been shown to significantly reduce TG, non-HDL-C and TG/HDL-C ratio, and lead to an improvement in LDL subpopulation pattern. 130,131 There are no trials of CDO evaluating clinical cardiovascular events in response to lifestyle changes initiated in childhood. However, better vascular health in adults can be related to healthy childhood risk status and behaviors, as shown in the Bogalusa Heart Study and in the Cardiovascular Risk in Young Finns study, where sustained low-risk status and healthy diet from childhood to adulthood was associated with thinner cIMT.…”
Section: Management Of Combined Dyslipidemia Lifestyle Changementioning
confidence: 99%
“…Diets higher in saturated fats have generally been related to larger more buoyant LDL particles than diets rich in monounsaturated or polyunsaturated fats [8]. Other studies have reported an increase in LDL size after supplementation with docosahexaenoic acid [9], but results are inconsistent [10]. …”
Section: Introductionmentioning
confidence: 99%